Manejo Integrado de Spodoptera frugiperda en el cultivo de Maíz (Zea mays L) - López Oseguera, Irving Rubén (2017)
SUMMARY This study seeks to improve knowledge about the integrated management of Spodoptera frugiperda in the cultivation of corn, which proposes to use all control methods to maintain its population at levels below the economic damage threshold. Through research in books and authors of theses related to the management of Spodoptera frugiperda, they suggest that the applications with biological products based on Bacillus thuringiensis can control up to 95% of the pest in the first stages at temperatures below 30ºC. This system of integrated pest management has an ecological approach, but in high economic thresholds as it is in most corn plantations, the use of chemical insecticides in 100 cc doses of Fipronil mixed in 120 pounds of sand is preferable, applying 3 g per plant. Some authors suggest other less toxic insecticides to avoid damage to the natural enemies of S. frugiperda, as long as they do not exceed the economic threshold of damage, such is the case of Abamectin that acts by ingestion and direct contact of movement and others.